C - reactive protein is a promising indicator of ventricular arrhythmias in pacemaker patients. (2nd May 2022) - Jirak, P; Mirna, M; Wernly, B; Hinterbuchner, L; Hauptmann, L; Fejzic, D; Topf, A; Lichtenauer, M; Hoppe, U; Hoefer, K; Schernthaner, C; Motloch, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Ventricular tachyarrhythmias are the main reason for sudden cardiac death to date. Accordingly, tools for risk stratification for ventricular arrhythmias are paramount. Non-sustained ventricular tachycardia (nsVT) represents a predictor of malignant rhythm disorders. Recently, low grade chronic inflammation was shown to predict ventricular arrhythmic events in high risk patients. This study aims to investigate, if inflammatory markers may predict higher arrhythmia burden in a low risk population. Methods: We prospectively analyzed ventricular arrhythmia burden in pacemaker records of 166 patients (age 79.2 9.3; male 60.2%, 38 with coronary artery disease (CAD)) with preserved ejection fraction (left ventricular ejection fraction≥50%) during a annually pacemaker follow up in a single center. To evaluate potential predictive factors, associations of laboratory values including inflammatory markers (CRP and interleukin 6) with occurrence of nsVT was evaluated using logistic regression. Sensitivity analysis in patients with and without established CAD was performed. Results: The cumulative incidence of nsVT was 12.7%. Concentrations of BNP (OR 1.00 95%CI 0.99-1.01; p=0.46), troponin (OR 0.98 95%CI 0.95-1.02; p=0.43) or interleukin-6 (OR 1.03 95%CI 0.99-1.07; p=0.16) were not associated with the occurrence of nsVTs. However, the concentration of CRP was associated with increased odds of nsVT (OR 1.26 95%CI 0.97-1.64; p=0.09) in trend. In sensitivity analysis in CAD patients, CRP was associated with increased likelihood of nsVT (OR 3.89 95%CI 1.14-13.29; p=0.03), whereas in patients without CAD there was no association between CRP and rates of nsVTs (OR 1.16 95%CI 0.88-1.54; p=0.30). Conclusion: Our study shows that inflammatory markers like CRP may be promising predictors of rhythm disorders CAD patients. While CRP was associated with increased odds for nsVTs in pacemaker patients with CAD, IL-6 did not show a significant correlation. This might be based on a more volatile expression of IL-6 while CRP represents a more stable parameter for inflammation.